Arthroscopic Ankle Fusion in the Post-Polio Paralytic Foot - Jimmy Joseph Meleppuram, M.S.Ortho.; Ayyappan V. Nair, D.Ortho., D.N.B.Ortho.; Hamdi Nizar Ahamed, M.S.Ortho.; Nizaj Nasimudeen, D.N.B.Ortho., M.R.C.S.; Ananthakrishnan Radhakrishnan, M.B.B.S.; Ajayakumar Thankappan, M.S.Ortho.; Prince Shanavas Khan, D.Ortho., M.S.Ortho. (Arthroscopy Techniques, 2025)
Post-polio residual paralysis can lead to severe musculoskeletal issues, including foot deformities and ankle instability, which can progress to end-stage arthritis. These complications cause significant pain and disability, dramatically impacting quality of life. Arthroscopic ankle fusion is a promising treatment option for addressing ankle joint dysfunction in post-polio patients. This technique discusses our experience with arthroscopic assisted ankle arthrodesis (tibiotalar fusion) to correct alignment and improve functionality in a post-polio residual paralytic foot.